2020
DOI: 10.1080/23311975.2020.1816419
|View full text |Cite
|
Sign up to set email alerts
|

Organisational learning and employee engagement: The mediating role of supervisory support

Abstract: This study examined the effect of organisational learning on employee engagement and the mediating influence of supervisory support in some selected pharmaceutical companies in Nigeria. The survey research design was adopted to assess the subject matter. Five hundred and forty-one hundred (541) respondents were surveyed across all the selected pharmaceutical companies in Nigeria with the usage of purposive and stratified sampling technique. Only four hundred and thirtyfour (434) copies of questionnaire represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Finally, as per recommendations to explore potential mediating factors in the relationship between OL and WE and improve our understanding of this relationship (Ogueyungbo et al, 2020), this study has identified that both ER and PE are significant mediators. Regarding the former, the findings of this research demonstrate that the impact of OL on WE occurs indirectly through ER.…”
Section: Discussionmentioning
confidence: 80%
“…Finally, as per recommendations to explore potential mediating factors in the relationship between OL and WE and improve our understanding of this relationship (Ogueyungbo et al, 2020), this study has identified that both ER and PE are significant mediators. Regarding the former, the findings of this research demonstrate that the impact of OL on WE occurs indirectly through ER.…”
Section: Discussionmentioning
confidence: 80%
“…Based on recommendations to research potential mediating factors in the relationship between LS, TC, JD, and WS [88], this analysis determined that JD are significant mediators. The aforementioned studies demonstrated that LS affected WS indirectly through JD (H5).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, good decision-making is important for managers at all levels, and employee participation in decision-making is essential. Employee participation was chosen because most civil service is characterized by top-bottom communication, with senior management laying out the policies, norms and procedures for the staff to follow (Ogueyungbo et al , 2020). As a result, there is little employee involvement in decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%